2006
DOI: 10.14236/ewic/ease2006.3
|View full text |Cite
|
Sign up to set email alerts
|

Software Modernization and Replacement Decision Making in Industry: A Qualitative Study

Abstract: Software modernization and replacement decisions are crucial to many organizations. They affect greatly to the success and well being of the organizations and their people. The decisions like that are usually presumed to be rational and based on facts. These decisions and how they are made tell much about the decision makers and the decision making tools available to them. Interviews of 29 software modernization decision makers or senior experts were analyzed in order to find out how the decisions were made an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, even if organizations get fully on board with openly incorporating and supporting sensory-based aspects of management learning, some managers may have difficulty overcoming years of school and corporate conditioning against sensing as a valid way of knowing. Learning to attend to sensing and interpret received signals may require breaking through barriers which include: preference for sequential reasoning style (Bakken et al, 2016), lack of sensory awareness (Krycka, 2014), not having adequate vocabulary to talk about sensory experiences (Taylor, 2002: 837), mistrusting one's senses (Dane, 2019), dismissing sensory perceptions (Burneko, 1997), discomfort with the process of mastery when it comes to sensing rather than analyzing (Ardichvili et al, 2003), getting over the established corporate social norms against sensing (Goldstein et al, 2008), and habitual denying of sensory input (Saarelainen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even if organizations get fully on board with openly incorporating and supporting sensory-based aspects of management learning, some managers may have difficulty overcoming years of school and corporate conditioning against sensing as a valid way of knowing. Learning to attend to sensing and interpret received signals may require breaking through barriers which include: preference for sequential reasoning style (Bakken et al, 2016), lack of sensory awareness (Krycka, 2014), not having adequate vocabulary to talk about sensory experiences (Taylor, 2002: 837), mistrusting one's senses (Dane, 2019), dismissing sensory perceptions (Burneko, 1997), discomfort with the process of mastery when it comes to sensing rather than analyzing (Ardichvili et al, 2003), getting over the established corporate social norms against sensing (Goldstein et al, 2008), and habitual denying of sensory input (Saarelainen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We observed this idea in action with managers' 'trusting-not-trusting' dance in organizations, not relying openly on sensing as a source of knowing because of their perception that colleagues in the organization may not accept it. Several participants in our corporate workshops described their reluctance to bring insights based on 'having a sense for a situation' to their teammates and managers in fear of being ridiculed (Saarelainen et al, 2006). Sensing alone is 'just not good enough' in the corporate culture of quantitative approach, according to the software engineers in our workshops.…”
Section: Corporate Social Norms Against Sensory Informationmentioning
confidence: 95%
See 1 more Smart Citation
“…The feasibility of exposing legacy system functionality as services within an SOA environment for an organization can be validated by Service Migration and Reuse Technique (SMART) processes [1]. The maintenance cost of legacy system would be between 40% and 90% of the total costs of the life cycle of the system [23]. Migrating the legacy systems to modernized and flexible technologies will yield -Reduced TCO (Total Cost Of Ownership), minimizes risk by moving off costly and outdated resources and adds value by maximizing the resource utilization of the infrastructure whereby energy efficiency is achieved.…”
Section: Legacy Featurementioning
confidence: 99%
“…Despite these challenges, organizations still find it difficult to abandon or replace them; rather, legacy modernization aimed at transformed the legacy application into modernized versions with features that address the fundamental challenges and possibly drive down maintenance cost is usually considered as the best option (Mishra, 2009). This fact is further affirmed in (Malinova, 2010), Comella-Dorda et al (2010); Saarelainen et al (2006) and Khadka et al (2010) where legacy modernization is reported as being more profitable than outright replacement with a caution that application must be replaced only when it can no longer be evolved.…”
Section: Introductionmentioning
confidence: 99%